Oxfold: kinetic folding of RNA using stochastic context-free grammars and evolutionary information. - Anderson, JWJ; Haas, PA; Mathieson, L-A; Volynkin, V; Lyngsø, R; Tataru, P; Hein, J (Oxford University Press (OUP), 2013)
MOTIVATION:Many computational methods for RNA secondary structure prediction, and, in particular, for the prediction of a consensus structure of an alignment of RNA sequences, have been developed. Most methods, however, ignore biophysical factors, such as the kinetics of RNA folding; no current implementation considers both evolutionary information and folding kinetics, thus losing information that, when considered, might lead to better predictions. RESULTS:We present an iterative algorithm, Oxfold, in the framework of stochastic context-free grammars, that emulates the kinetics of RNA folding in a simplified way, in combination with a molecular evolution model. This method improves considerably on existing grammatical models that do not consider folding kinetics. Additionally, the model compares favourably to non-kinetic thermodynamic models.